Celiac disease screening in children: evaluating the evidence, benefits, and challenges - Naredi Scherman, Maria; Melin, Jessica; Agardh, Daniel (Frontiers in Pediatrics, 2025)
Comprehensive screening of the general population is the only approach capable of identifying the majority of cases with celiac disease. In 2023, the Italian Parliament enacted a law to implement nationwide screening for celiac disease and type 1 diabetes. However, critical decisions regarding the target population, optimal timing, and screening methods remain unresolved. Previous observational studies on birth cohorts of children with genetic risk for these conditions have demonstrated that the incidence peaks early in life and is influenced by HLA risk genotypes. This mini-review explores different aspects of screening for celiac disease, presenting the advantages and challenges of identifying children before onset of symptoms. In addition, we summarize the current knowledge and gaps in understanding related to screening programs for celiac disease in children and adolescents and discuss health benefits, psychosocial aspects and cost-effectiveness, and their potential implications for future public health strategies.